A COMPARATIVE STUDY ON DIABETIC FOOT ULCERS LEADING TO AMPUTATIONS - Rehman, Romisa; Malik, Farhat Rehana; Rehman, Zarlish (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine and compare the frequency of foot ulcers leading to amputations in relation to gender, type and duration of diabetes. Methodology: A descriptive study conducted at three teaching hospitals of Peshawar, from November-2015 to February-2016. Data was collected using convenient sampling technique via semi structured questionnaire. Inclusion cri- teria were diabetic, non-smoker, having no visible deformity other than ulcer or amputation; while critically ill patients, children less than 13 years, gestation- al diabetics and who did not consent upon were excluded. One hundred and twelve diabetics (type 1 & type 2) were included in the study. The collected data were entered and analyzed in SPSS version 23. P values were computed and significance level was set at <0.05. Results: Mean age was 53.55 ±11.58 years. Twenty four males (60%) had foot ulcers and among them, 16 (40%) got their lower leg amputated, whereas 55.5% females had foot ulcers and 24 (33%) among them had amputations. Type 1 diabetics with foot ulcers were 44 (72%) while type 2 diabetics were 68 (47%). Diabetic foot ulcers were found to be highly significant with type of dia- betes (p value =0.007). Duration of illness more than 11 years was found to be a risk factor in 90% of amputations. Conclusion: Diabetic foot ulcers were reported more in males and were found to be highly significant with type of diabetes.